Una aventura más allá del Mar Tenebroso: el Monomotapa - Fraticelli, Barbara (Revista de Filología Románica, 2006)
Portuguese travellers, in the XVIth and XVIIth centuries, in their expeditions through the African continent, from the Mozambican coast, discovered a country with its own hierarchy and an absolute king, the Monomotapa, whose habits contributed to create a literary image of this culture across Europe which is more mythological than real.